Literature Review: Dampak Warfarin terhadap Risiko Kanker - Maleeka Jasmine Nadzira Ramadhani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Venous Thromboembolism (VTE) is a common complication in cancer patients. The treatment of VTE in cancer patients involves anticoagulant therapy using Vitamin K Antagonists (VKAs), including warfarin. VTE can be managed with warfarin administration, typically preceded by bridging therapy with heparin. The objective of this literature review is to examine and analyze studies related to the impact of warfarin use on cancer risk. The review was conducted on articles published in English over the past 10 years (2013–2024) using electronic databases such as Google Scholar and PubMed. The findings suggest that warfarin may be associated with improved overall survival in cancer patients and may have protective effects against certain types of cancer. Warfarin may exhibit antineoplastic properties through mechanisms both dependent on and independent of coagulation pathways, the latter mediated by the inhibition of the GAS6-AXL signaling pathway.